Physiologic response to distance diving in healthy children and young adults - Feige, Sasika; Peter, Sophie; Weickmann, Johannes; Michaelis, Anna; Gebauer, Roman Antonin; Weidenbach, Michael; Dähnert, Ingo; Münch, David; Poschart, Max; Wüstenfeld, Jan; Paech, Christian (Frontiers in Sports and Active Living, 2025)
IntroductionDiving and fin swimming are well established sports, including competitive sports, but little is known about the short-term adaptation of physiological parameters in Children and Adults during submersed dynamic apnea near the individual maximum. The current study provides data on the physiological adaptation of Children and young Adults to dynamic apnea diving in real—life conditions.MethodsThis study provides data from 11 healthy elite fin swimmers (<30 years), including transcutaneous oxygen saturation and heart rate performing various diving protocols.ConclusionThe results suggest that apnea duration primarily affects oxygen saturation, while dive speed influences cardiovascular workload. Oxygen levels often decline post-dive, indicating a delayed oxygen debt requiring recovery. Future research should explore broader demographics, including recreational divers and medically restricted populations.